Research Article Screening of Alkaline phosphatase activity in Bacteria - Hasan, Hamid Ghaffoori; babu, Neerugatti Dora (International Journal of Psychosocial Rehabilitation, 2020)
The study was conducted in the pathological analysis department during the period from 13th. NOV. To 30th. MAR 2017. Specimens used were different species of bacterium, by applying ALP activity determination in the broth of the bacterium species. The study reflects a higher total activity of ALP in Proteus species than the other species. While, specific activity was seen in E.Coli.